Natural ghrelin in advanced cancer patients with cachexia, a case series. Issue 2 (15th January 2021) - Blum, David; de Wolf‐Linder, Susanne; Oberholzer, Rolf; Brändle, Michael; Hundsberger, Thomas; Strasser, Florian
Abstract: Background: Natural ghrelin, a peptide growth hormone secretagogue, has a therapeutic potential in cachexia. We designed a dose‐finding trial of subcutaneous natural ghrelin to improve nutritional intake (NI) in advanced cancer patients. Methods: Advanced cancer patients with cachexia management (symptom management, physiotherapy, nutritional, and psychosocial support) started with ghrelin at 32 μg/kg body weight, followed by 50% dose increases. Patients self‐injected ghrelin twice daily for 4 days followed by a wash‐out period. After reaching the primary endpoint, maximal NI (minimal dose for maximal NI), a maintenance period followed during which patients injected 10 doses of ghrelin per week. Safety parameters, NI, and cachexia outcomes (symptoms, narratives, muscle mass, and strength) were measured over 6 weeks. Results: Ten patients with metastatic solid tumours were included, and six (100% male, mean age 61.8 ± 8.5 SD) received ghrelin. Minimal dose for maximal NI was reached in four patients. Three patients reached the end‐of study visit. Ghrelin was well tolerated with variable results on appetite and eating‐related symptoms but a positive effect in the narratives. Mean Functional Assessment of Appetite & Cachexia Therapy score was 6.8 points lower at final measurement compared with baseline, t (5) = 5.98, P  < .01. Muscle mass was stable in two patients and increased in one patient, and muscle strength was stable in three patients. Subjective tolerability was high. Patients showed a fluctuating trajectory, and median survival was 88 days (51–412 days). Conclusions: Ghrelin was safe in advanced patients with cancer cachexia without dose‐limiting toxicity and well tolerated. The intervention was very complex, and the number of patients included was small. There was a positive effect on nutritional intake and patient narratives.